Transition between SU(4) and SU(2) Kondo effect - Tosi, Leandro (2012)
Motivated by experiments in nanoscopic systems, we study a generalized Anderson, which consist of two spin degenerate doublets hybridized to a singlet by the promotion of an electron to two conduction bands, as a function of the energy separation d between both doublets. For d¼0 or very large, the model is equivalent to a one-level SU(N) Anderson model, with N¼4 and 2 respectively. We study the evolution of the spectral density for both doublets (r 1s ðoÞ and r 2s ðoÞ) and their width in the Kondo limit as d is varied, using the non-crossing approximation (NCA). As d increases, the peak at the Fermi energy in the spectral density (Kondo peak) splits and the density of the doublet of higher energy r 2s ðoÞ shifts above the Ferrmi energy. The Kondo temperature T K (determined by the half-width at half maximum of the Kondo peak in density of the doublet of lower energy r 1s ðoÞ) decreases dramatically. The variation of T K with d is reproduced by a simple variational calculation.